Radiocarbon dating reveals the timing of formation and development of pedogenic calcium carbonate concretions in Central Sudan during the Holocene. (1st October 2018) - Dal Sasso, Gregorio; Zerboni, Andrea; Maritan, Lara; Angelini, Ivana; Compostella, Chiara; Usai, Donatella; Artioli, Gilberto
Abstract: Calcic soil horizons are common in arid and semi-arid lands and represent the result of the progressive accumulation of calcium carbonate in the soil profile over time. This process leads to the occurrence of several pedogenic phases of calcium carbonate dissolution/precipitation. For this reason, timing the formation and development of calcic horizons through radiometric dating is not straightforward as time-averaging effects, due to the superimposition of the same process over time, occur. On this basis, this study aims to define the timing and dynamics of formation and development of pedogenic calcium carbonate concretions from semi-arid Central Sudan, highlighting the relevance of a multi-disciplinary approach and the effectiveness of radiocarbon dating (coupled to an accurate sampling strategy) applied to pedogenic carbonates. Calcic soil horizons (Bk) were sampled during the archaeological excavation of site 16-D-4 at Al Khiday (Central Sudan) and studied by optical, cathodoluminescence and scanning electron microscopy, as well as by chemical-physical and stable isotopes (C and O) analyses. Micromorphological analyses reveal the occurrence of distinctive calcitic pedofeatures, here described as calcitic-cemented nodules and calcitic-rich matrix. Radiocarbon ages obtained for these pedofeatures mostly refer to the Early Holocene for calcitic-cemented nodules (11.5, 9.9 and 9.6 cal. ka) and to the Middle Holocene for powdery calcitic-rich matrix (7.9, 7.7, 6.3 and 6.1 cal. ka) samples. Additionally, δ 13 C and δ 18 O values indicate major shifts of environmental conditions from the Early to the Middle Holocene, in agreement with the available information from detailed palaeoenvironmental studies carried out in the region. In particular, Early Holocene pedogenic calcitic features can be related to short arid phases during general wetter climate conditions, whereas those formed in the Middle Holocene can be related to short humid phases. Results show that Bk horizons were characterized by alternate periods of calcite accumulation (precipitation) and dissolution, and periods of quiescence or extremely slow growth rates. Thus, the formation and development of Bk horizons have been a long-lasting process significantly influenced by climatic fluctuations. This study represents a further step in the comprehension of the development of calcium carbonate concretions and (at a wider perspective) calcrete; the paper also contributes to the definition of a reliable method to radiometrically date the formation of calcic pedofeatures. On a broader perspective, this work may offer a significant tool for archaeometric studies, where the interaction between secondary calcite and archaeological material is significant (e.g., radiocarbon dating of bioapatite in bones), and palaeoenvironmental studies in arid lands, where Bk horizon development is a function of past rainfall.